The Classroom Social Environment: A Case Study On Engineering Technology Students’, FTK, UTEM - Hamzah, Khairum; Zainal, Nurul Amira; Kashi'ie, Najiyah Safwa; Waini, Iskandar; Hairol Anuar, Siti Haryanti; Hussin, Nor Hafizah (IJHSSI, 2015)
-